Preparing for the Future Crisis: Lessons from Creative Economic Policies on Micro, Small, and Medium Enterprises in Pandemic - Putra, I Made Arie Widyasthana Wartana; Sajida, Sajida (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2023)
Looking at how the government implements creative economy policies for the Micro, Small, and Medium Enterprises (MSME) sector during a pandemic, this article aims to see how they are implemented and draw lessons that can be used to prepare for future crises. This study aims to identify the challenges that the creative economy in MSME will face in the future, so that a number of suggestions can be provided as capital for defense and strengthening of the national economic sector. This study's research chosen method is a literature review, with primary sources consisting of scholarly journal articles from various sources. This study demonstrates how government economic policies can increase MSMEs' product sales. According to the findings of the analysis, there are two tailed of issues that will be confronted in the future, systemic and dynamic challenges. As a result, the MSME sector should be ready to improve the system and adapt it to the market environment.